Project Termination Decisions, Underinvestment and Overinvestment* - TAN, PATRICIA M. S. (Contemporary Accounting Research, 2000)
Abstract In this article, I use the principal‐agent framework to examine the incentives of risk‐and work‐averse agents to work on projects that are long‐term, multistage, and subject to abandonment. Periodic applications of effort by the agent are required. The agent also obtains private information as the project evolves, and he decides whether the project should be abandoned or continued. The principal not only seeks to provide incentives to induce the agent to take up such risky investments and work hard at them, but also seeks to provide incentives for the agent to abandon the project if the profit prospect is low. We show that the agent's decision to continue is not always aligned with the principal's desire. The result provides an economic rationale for the sunk cost phenomenon. There also exist conditions under which the agent chooses to prematurely abandon the project.